Implementasi Program Accurate Online Dengan System Serta Laporan Stock Pada Perusahaan - Adrian, Adrian; Chandra, Dicky Joman; Priscillia, Audrey (Jurnal Pengabdian Masyarakat Inovasi, 2025)
Digital transformation in accounting systems is a strategic step for manufacturing companies like Roti ROMI to improve stock data accuracy and financial reporting efficiency. This community service activity aims to provide assistance and training on the implementation of cloud-based accounting software, namely Accurate Online, to employees and youth within the Roti ROMI environment. The main problem faced by the partner prior to this activity was the disorganized recording of raw materials and finished goods, which was still done manually using Excel, leading to frequent data discrepancies. The implementation method included problem identification, planning using the 5W+1H system, implementation through interactive lectures and live simulations via Zoom Meeting, and an evaluation phase using pre-tests and post-tests. The results of the activity showed a significant increase in participants' understanding of critical features such as item stock, inter-divisional item transfer, and item requisition. Employees are now able to prepare organized stock reports and monitor inventory in real-time through the system. The involvement of Politeknik Cendana students also accelerated the knowledge transfer process through intensive technical assistance. The conclusion of this service confirms that the use of Accurate Online has a positive impact on management in monitoring company operations transparently. This success is expected to motivate partners to fully transition to technology-based financial reporting to accelerate the process of preparing accurate reports in the digital era.